Why swimmers slow down - Rushall, B. S. (NSW Swimmer Online Magazine, 1993)
On the amount of resistance, more commonly referred to as "drag," that is created by the swimmer and may be the cause for that some swimmers look to be swimming well at slow speeds but when they attempt to speed up they do not improve as much as others. A suitable classification of drag for swimming contains three types of drag, each arising from different physical mechanisms and detracting from performance in different amounts: 1. Frictional Drag 2. Form Drag 3. Wave Drag The technique of swimming fast must be efficient and produce the least resistance possible. Attention to drag factors will contribute to propelling efficiency and will make swimming fast a lot easier and rewarding.